(untitled) (Third Sector Social Economic Review, 2022)
Marketing activities are influenced by the society in which it is located. The religious element that constitutes the cultural structure of the society can also be decisive in this sense. In this study, it has been tried to reveal which visual elements are provided with this change in the advertising posters specially designed for the month of Ramadan. Advertising posters used for the same products in other periods were also shared, and the difference was tried to be revealed. Common elements that stand out in the analyzed posters were found, and it was determined that they were differentiated according to important periods in terms of consumers’ beliefs. Since fasting is observed throughout the day in Ramadan, there may be more interest in products to be eaten at iftar. Businesses that take into account this periodical change of perception of the consumer plan their advertising activities accordingly. Like many types of advertisements, poster advertisements are also affected by this change. It is seen that beverage brands make advertising posters during Ramadan by using parts such as iftar time or after iftar in these advertising posters. The semiotic analysis method was used in the study to examine how beverage brands promote their products on their advertising posters and how they reflect Ramadan. The semiotic method is a method used in the field of advertising. It shows the strings with meaning in a text and with the help of semiotics, it is an approach that aims to read the visual, give meaning to the codes, evaluate the relationships between the texts with strings, syntax, metaphor and connotation, and reveal ideologies and cultures with indirect meanings. In this study, Ramadan advertisement posters of Pınar Limonata, Beyoğlu Gazoz, Coca Cola and Sırma brands were preferred in order to make semiotic analysis. In order to analyze how they reflect the month of Ramadan, semiotics, sign analysis, visual expression, code analysis, serial and syntactic solutions have been tried to be made.